Removal of Organic Matter from Landfill Leachate by Advanced Oxidation Processes: A Review - Wei Li; Qixing Zhou; Tao Hua (International Journal of Chemical Engineering)
In most countries, sanitary landfill is nowadays the most common way to eliminate municipal solid wastes (MSWs). However, sanitary landfill generates large quantity of heavily polluted leachate, which can induce ecological risk and potential hazards towards public health and ecosystems. The application of advanced oxidation processes (AOPs) including ozone-based oxidation, Fenton oxidation, electrochemical oxidation, and other AOPs to treatment of landfill leachate was reviewed. The treatment efficiency in term of chemical oxygen demand (COD) of various AOPs was presented. Advantages and drawbacks of various AOPs were discussed. Among the AOPs reviewed, Fenton process should be the best choice, not only because it can achieve about 49~89% of COD removal with COD ranging from 837 to 8894 mg/L, but also because the process is cost-effective and simple in technological aspect, there is no mass transfer limitation (homogeneous nature) and both iron and hydrogen peroxide are nontoxic.